2014
DOI: 10.1089/thy.2013.0119
|View full text |Cite
|
Sign up to set email alerts
|

Thyrotropin Isoforms: Implications for Thyrotropin Analysis and Clinical Practice

Abstract: Serum thyrotropin (TSH) is considered the single most sensitive and specific measure of thyroid function in the general population owing to its negative logarithmic association with free triiodothyronine and free thyroxine concentrations. It is therefore often the test of choice for screening, diagnosis, and monitoring of primary hypothyroidism. Serum TSH concentrations can be analyzed quantitatively using third-generation immunoassays, whereas its bioactivity can be measured by TSH activity assays in cell cul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(35 citation statements)
references
References 157 publications
2
32
0
Order By: Relevance
“…The TSH to free T 4 relationship is frequently altered in the ambulatory elderly due to changes independent of thyroid gland failure (14,21,28,39). Two cohort studies have shown that aging is associated with an increase in TSH without a fall in free T 4 (26,27).…”
Section: Elevated Tsh Values In the Elderlymentioning
confidence: 99%
See 3 more Smart Citations
“…The TSH to free T 4 relationship is frequently altered in the ambulatory elderly due to changes independent of thyroid gland failure (14,21,28,39). Two cohort studies have shown that aging is associated with an increase in TSH without a fall in free T 4 (26,27).…”
Section: Elevated Tsh Values In the Elderlymentioning
confidence: 99%
“…TSH concentrations are currently measured using third-generation immunoassays, which may reflect increased immunoactive but not bioactive TSH, as in the elderly (28). In the future, new technologies for TSH measurements that quantitate only bioactive TSH may help to accurately identify chronically ill patients with mild thyroid gland failure (28).…”
Section: What Is the Underlying Etiology Of Isolated Tsh Elevations? mentioning
confidence: 99%
See 2 more Smart Citations
“…From a laboratory point of view, the definition of universally applicable TSH-thresholds seems questionable as well, considering the inter-platform variation between TSH assays. As each manufacturer produces distinct TSH-recognizing antibodies, variation in TSH-epitope recognition and binding-affinity is to be expected, which is also influenced by post-translational modifications of TSH (17). Apart from this between-method variation, the TSH and fT 4 reference intervals applied by an individual laboratory are of crucial influence in the correct clinical classification of thyroid conditions.…”
Section: Introductionmentioning
confidence: 99%